ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN EARLY WARNING SYSTEM PADA PERUBAHAN KLINIS PASIEN DI RUMAH SAKIT X - Dian Indriani Hidayat; Farid Agushybana; Sri Achadi Nugraheni (Dian Nuswantoro Semarang, 2020)
Early Warning System (EWS) is an information system on patient care that needed to support decision making of patient’s clinical change. The impact of EWS usage on patient’s clinical change still varies therefore a question raised whether EWS usage will improve hospital service quality. The lack of information on factors related to EWS usage effectivity became the reason to conduct this study. The study aimed to understand the factors that relates to EWS usage. The study was a cross sectional approach. Population in the study was 297 EWS healthcare users in X Hospital. Sample taken in the study was 168 healthcare users with proportionate stratified random sampling method. EWS usage data were collected from medical records audit. Factors related to EWS usage data was taken from questionnaire. Relationship between factors and EWS usage were analyzed by using Chi square test and logistic regression test. Proper EWS usage on patient’s clinical change in X Hospital general ward was very low. System quality, user satisfaction and organization structure independently were significant related to EWS usage. Organization structure and user satisfaction have an impact as 12.374 times and 4.671 times to the use of EWS system.Keywords: EWS; General ward; Service qualitiy